Inclusion of Azolla pinnata as an unconventional feed of Zaraibi dairy goats, and effects on milk production and offspring performance - Hassanein, Hanan A. M.; Maggiolino, Aristide; Abou El-Fadel, Magdy H.; De Palo, Pasquale; El-Sanafawy, Heba A.; Hussein, Ahmed M.; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2023)
This study investigated the effects of using sun-dried Azolla (Azolla pinnata) meal (SDAM) protein to replace sunflower meal protein in the diets of Zaraibi goat dams on nutrient digestibility, milk yield, composition, and economics. A total of 15 Zaraibi goats (32.23+0.2 kg) were randomly divided into three equal groups, R1, R2, and R3 which were fed based on average milk production. The basal ration was a concentrated feed mixture containing 0, 10 and 20% SDAM which replaced 0, 25, and 50% of sunflower meal protein in the respective groups. The results revealed significantly higher (P<0.05) mean milk yield in the SDAM groups in comparison to R1. The beneficial effects of the tested groups were observed in milk composition, milk fat, milk protein, and non- fats solids. whereas the milk fat yield was higher in the SDAM group in comparison with the control group. Ration inclusion of SDAM improved economic feed efficiency and had a significant effect on the yield of milk constituents. In general, using up to a level of 20% SDAM in place of sunflower meal for feeding lactating Zaribi goats improved milk production, milk fat yield, and cost -benefit ratio.